The Effect of Covid-19 Pandemic on Children's Fear, Anxiety and Depression Levels - Ibrahim Ozlu; Zeynep Ozturk; Zeynep Karaman Ozlu; Beyzanur Kiziloglu (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Aim: The purpose of this study is to determine the effect of the COVID-19 pandemic on children's fear, anxiety and depression levels. Method: The research was conducted in a descriptive and relationship seeking manner. From different provinces of Turkey's population of the study participants was created to reach online survey. The sample consisted of volunteer participants who agreed to participate in the study and were not infected with COVID-19. The research was completed with 304 children. The data were collected using the Personal Information Form, “The Fear of COVID-19 Scale and the Child Depression and Anxiety Scale. The coding and evaluation of the data were done in computer environment using SPSS 21 package program. In evaluating the data, number, mean, percentage distributions, standard deviation, Cronbach alpha coefficient and Pearson Correlation analyzes were used. Results: It was determined that the mean total score of the participants on the depression scale was 20.81 ± 5.55, the total score average of the anxiety scale was 31.81 ± 7.60, and the total score average of the COVID-19 fear scale was 18.82 ± 5.28. It was determined that there was a statistically significant positive correlation between the anxiety and depression total score averages of the participants and the fear of COVID-19 total score averages. Conclusion: It was found that during the period of the COVID-19 pandemic, children experienced moderate levels of fear of COVID-19, depression and anxiety. In addition, it was determined that the fear of COVID-19 experienced by children was associated with their depression and anxiety levels